STAR-EM: An innovative summer research program for medical students. Issue 4 (July 2020) - Friedman, Steven Marc; Porplycia, Danielle
ABSTRACT: We describe a novel 10-week summer research program aimed at developing academic emergency medicine (EM) interest among medical students. A cohort of students was recruited to participate in the Summer Training and Research in Emergency Medicine (STAR-EM) program with the primary goal of completing and disseminating a scholarly project. Curriculum development and program evaluation were informed by Kern's model and Kirkpatrick's hierarchy, respectively. Students and faculty demonstrated interest in academic EM and research productivity during the curriculum. This program provides a model for other emergency departments seeking to foster the development of academic EM at their institution.